Concordance, disease progression, and heritability of coeliac disease in Italian twins. Issue 6 (14th December 2005) - Nisticò, L; Fagnani, C; Coto, I; Percopo, S; Cotichini, R; Limongelli, M G; Paparo, F; D'Alfonso, S; Giordano, M; Sferlazzas, C; Magazzù, G; Momigliano-Richiardi, P; et al.
Abstract : Background and aims: We adopted the twin method to disentangle the genetic and environmental components of susceptibility to coeliac disease (CD). We estimated disease concordance rate by zygosity and HLA genotypes, discordance times, progression rates to disease, and heritability. Methods: We crosslinked the Italian Twin Registry with the membership lists of the Italian Coeliac Disease Association and recruited 23 monozygotic (MZ) and 50 dizygotic (DZ) twin pairs with at least one affected member. Zygosity was assigned by DNA fingerprinting, and HLA-DQ and DR alleles were genotyped. Disease status was ascertained by antiendomysial, anti-human tissue transglutaminase antibodies, and bowel biopsy. Results: Concordance was significantly higher in MZ (83.3% probandwise, 71.4% pairwise) than in DZ (16.7% probandwise, 9.1% pairwise) pairs. Concordance was not affected by sex or HLA genotype of the co-twin and being MZ was significantly associated with the occurrence of CD (Cox adjusted hazard ratio 14.3 (95% confidence interval 4.0–50.3)). In 90% of concordant pairs the discordance time was ⩽2 years. MZ and DZ co-twins had 70% and 9% cumulative probability of having symptomatic or silent forms of CD, respectively, within five years. Under ACE (additive genetic, common, and unshared environmental factors) models, with CD population prevalences of 1/91 and 1/1000, heritability estimates were 87% and 57%, respectively. Conclusion: MZ pairs have a high probability of being concordant, regardless of sex or HLA genotype. Most of the affected co-twins receive a diagnosis within two years. A remarkable proportion of phenotypic variance is due to genetic factors.